The role of research-based spin-offs in innovation ecosystems - Conceição, O.; Sousa, C.; Fontes, M. (International Journal of Education Economics and Development, 2024)
The objective of the paper is to contribute to a better understanding of the various roles played by research-based spin-offs (RBSOs) in knowledge dissemination. It investigates if RBSOs act as connectors and knowledge translators, both between different types of organisations within an innovation ecosystem and across different geographical scales and knowledge environments. This latter role has been relatively less investigated but is important to open local innovation ecosystems. The paper analyses the networks formed by Portuguese RBSOs in the context of research, technology and product development projects. The results suggest that RBSOs play an intermediary role in the country's innovation ecosystem, which can assume different forms. In the national networks, they frequently bridge research and downstream organisations, contributing to the dissemination of knowledge within the ecosystem. In the international networks, their most important role may be as connectors and conveyors of advanced knowledge produced in external knowledge environments.